1995
DOI: 10.1016/1074-7613(95)90179-5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of autoantibody production: Dominant localization of antibody-producing cells to T cell zones in fas-deficient mice

Abstract: The goal of this study was to examine the in vivo site of autoantibody production in normal and autoimmune-prone mice. B cells were identified in tissue sections with IgM- and IgG2a-specific riboprobes that readily distinguished resting cells from antibody-forming cells (AFC). In normal mice, the few identifiable IgG2a-secreting cells were found in the red pulp. By contrast, in Ipr mice exceedingly high numbers of IgG2a and autoantibody-producing cells were found deep within the T cell-rich periarteriolar lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
53
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 54 publications
11
53
0
Order By: Relevance
“…This occurred not just in the bridging channels, as would be expected (53,54), but also in high concentration in the T cell area. The same pattern of AFC cell distribution has been observed previously by Marshak-Rothstein and colleagues (72) in another cGVH model, as well as in the conventional anti-DNA 3H9 transgenics on an autoimmune background (12,55). Further investigation should help determine what causes these AFC to congregate in the T cell area.…”
Section: The Loss Of Anti-dsdna B Cell Tolerance Can Be Tracked In a supporting
confidence: 49%
See 1 more Smart Citation
“…This occurred not just in the bridging channels, as would be expected (53,54), but also in high concentration in the T cell area. The same pattern of AFC cell distribution has been observed previously by Marshak-Rothstein and colleagues (72) in another cGVH model, as well as in the conventional anti-DNA 3H9 transgenics on an autoimmune background (12,55). Further investigation should help determine what causes these AFC to congregate in the T cell area.…”
Section: The Loss Of Anti-dsdna B Cell Tolerance Can Be Tracked In a supporting
confidence: 49%
“…Additionally, a high concentration of darkly stained ϩ cells was present in the PALS, as well as in the bridging channels of the red pulp. This pattern of darkly staining cells, which presumably reflects intracytoplasmic Ig, has been correlated with AFC in several models (12,(52)(53)(54)(55). Curiously, the same pattern was also observed in bm1233H9(Ϫ) mice.…”
Section: Activation Status and Localization Of ϩ Cells After Cgvh Indsupporting
confidence: 48%
“…The major observation is that TLR2-and 4-deficient B6 lpr/lpr mice exhibit a lower proportion of MZ B cells than B6 lpr/lpr mice that could constitute another factor contributing to the decreased production of autoantibodies directed against TI Ags. Indeed, several works have shown that the autoantibody response, notably in MRL-Fas lpr/lpr mice, does not occur in the germinal centers but takes place at extrafollicular sites similar to those involving TI responses (44). This is particularly demonstrated for RF-secreting B cells and highly suspected for DNA-specific B cells (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Germinal centres in the spleen and LN are areas of intense proliferation of antigen-specific B cells. Such localization was not possible in the MRL/ lpr strain because the anatomic organization of the spleen is disrupted due to the accumulation of T lymphocytes expressing the CD4 7 CD8 7 B220 + phenotype (Jacobson et al, 1995). Regardless of the strain, the striking feature of splenic ISH was the ringlabelling pattern encircling a weakly labelled nucleus ( Figure 2C,a), which shows the presence of LINE-1 sense-strand transcripts in the cytoplasm.…”
Section: Line-1 Orf2 Transcription Of Sense and Antisense Strands In mentioning
confidence: 99%